Sponsorship Marketing to Maintain Brand Image in Digital Age: Case Study of Kompas Daily's Special Events - Tarrence Karmelia Kontessa (2020)
Facing the digital era, print media face an increasing risk of disruption due to the paperless trend. Kompas Daily made various efforts to maintain its brand image like organizing some special events. This research limits itself to the question of how Kompas Daily manages its various special events, by utilizing its strengths and resources as the largest Indonesia's print media, and by designing a good event management to strengthen the company's brand image. The method used is a case study with a descriptive qualitative approach. Data are collected through interviews, observation and literature study and then tested by triangulation techniques. The results showed Kompas Daily succeeded in develop an event management proven to be able to strengthen Kompas Daily's brand image, and even succeeded in making the special events as a new revenue stream.